Analisis Dan Perancangan Sistem Informasi Manajemen Aset Berbasis Web Pada Kantor Dinas Pendidikan Provinsi Jambi - Nurdani, Rahmat; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2020)
Education Board of Jambi Province is a public service which its main task is to provide service to the development sector in Senior High School (SMA), development sector in Vocational School (SMK), Educational Personnel sector (GTK) and Special Education and Special Service (PKLK). The asset management in the office of the Education Board in Jambi Province is processed in a conventional way and using Ms. Excel so that the performance of the management asset system is still not optimal yet. One of the ways to make asset management to be more optimal is by using an information system. The study of asset management carried out at the planning stage, the procurement stage and the reporting stage. This study results in a prototype system that illustrates the planning, procurement, and reporting of the asset to the Education Board in Jambi Province. The method used in this study is the object-oriented approach by using Data Flow Diagram (DFD), Entity-Relationship Model (E-R Model), i.e. the relation between table, context diagram and flowchart. This study also results in a prototype which can be implemented further to produce an information system of asset management with web-based which can be implemented in the Education Board in Jambi Province